Ferroelectric columnar assemblies from the bowl-to-bowl inversion of aromatic cores - Shunsuke Furukawa; Jianyun Wu; Masaya Koyama; Keisuke Hayashi; Norihisa Hoshino; Takashi Takeda; Yasutaka Suzuki; Jun Kawamata; Masaichi Saito; Tomoyuki Akutagawa (Nature Communications, 2021)
Organic ferroelectrics are of potential use in state-of-the-art ferroelectric devices but mechanistic insight in generating ferroelectricity remains limited. Here, the authors demonstrate that a bowl-to-bowl inversion of a bowl shaped organic molecule generates ferroelectric dipole relaxation, extending the concept of ferroelectricity in small organic molecules.